Sex-Based Differences in Autologous Cell Therapy Trials in Patients With Acute Myocardial Infarction: Subanalysis of the ACCRUE Database - Haller, Paul M.; Gyöngyösi, Mariann; Chacon-Alberty, Lourdes; Hochman-Mendez, Camila; Sampaio, Luiz C.; Taylor, Doris A. (Frontiers in Cardiovascular Medicine, 2021)
Background: Sex-based differences are under-studied in cardiovascular trials as women are commonly underrepresented in dual sex studies, even though major sex-based differences in epidemiology, pathophysiology, and outcomes of cardiovascular disease have been reported. We examined sex-based differences in patient characteristics, outcome, and BM-CD34+ frequency of the ACCRUE (Meta-Analysis of Cell-based CaRdiac studies) database involving patients with acute myocardial infarction (AMI) randomized to autologous cell-based or control treatment. Methods: We compared baseline characteristics and 1-year follow-up clinical data: composite major adverse cardiac and cerebrovascular events (primary endpoint), and changes in left ventricular ejection fraction (LVEF), end-diastolic (EDV), and end-systolic volumes (ESV) (secondary efficacy endpoint) in women and men (N = 1,252; 81.4% men). Secondary safety endpoints included freedom from hard clinical endpoints. Results: In cell-treated groups, women but not men had a lower frequency of stroke, AMI, and mortality than controls. The frequency of BM-CD34+ cells was significantly correlated with baseline EDV and ESV and negatively correlated with baseline LVEF in both sexes; a left shift in regression curve in women indicated a smaller EDV and ESV was associated with higher BM-CD34+ cells in women. Conclusions: Sex differences were found in baseline cardiovascular risk factors and cardiac function and in outcome responses to cell therapy.